SIMULACIÓN MEDIANTE DINÁMICA MOLECULAR DE LOS CAMBIOS ESTRUCTURALES DURANTE LA COLISIÓN DE NANOPARTÍCULAS DE COBRE - Copa, Betty (2009)
Molecular dynamics simulations with embedded-atom potential (EAM) have been performed to study the energetic and structural changes during the collision and coalescence of two Cun nanoparticles. We simulated collision of nanoparticles at several temperatures below the melting point and with different impact energy. Analyzing the potential energy change during the collision we identify three clearly defined stages. The pair correlation function and the pair analysis technique are used to reveal the structural changes in the collision process. The variation in the time of the population of different pairs has been quantified, being observed diverse structural transformations. During the collision of two equal icosahedral nanoparticles ( Cu55 ) has been observed different behavior of 1551 pairs depending on the impact velocity.